Motivation, governance, efficacy and contribution: a social practice model of commons-based peer production. (14th June 2019) - Wang, Rong
This study examines how individual motivation and governance structure of online collaboration affect individual contribution and efficacy in a commons-based peer production (CBPP) community. Using survey data and structural equation modelling, this study demonstrates motivational factors alone cannot fully predict CBPP outcomes. How people perceive their freedom in setting their own agenda affects their confidence in producing artefacts for reuse. It also provides evidence that how individuals perceive their own ability in peer production significantly affects their relationships with the collective. Built upon a social practice view, this study highlights that efficacy at both individual and community levels should be viewed as important outcomes of cooperative human activity. This study contributes to the literature on CBPP and virtual communities by demonstrating the value of open governance and self-efficacy.